THE ANALYSIS FISCAL CORRECTION IN THE CALCULATION OF INCOME TAX AGENCY: PT CAHAYA SEMESTA BERSAMA - Sirait, Rasisca; Hutajulu, Fharel M.; Lumbantoruan, Rutman (Universitas Kristen Indonesia, 2017)
In the analysis performed on the income statement of commercial PT. Light the Universe Together obtained positive fiscal correction Rp. 157 312 678 while the number of negative fiscal correction Rp. -240 438 974. These results indicate the existence of differences between accounting profits and profits for tax purposes. Commercial profit for 2015 amounted to Rp. 2238427655 whereas the taxable income of Rp. 2,155,301,359 and the amount of corporate income tax on PT. Light the Universe Together is Rp. 487 205 085. The conclusion from this research that the taxation policy applied by PT. Light the Universe Together with the conduct of fiscal correction in accordance with the regulations and taxation law. The cost is a constraint only zakat corrected positively to a company PT. Light the Universe Together, while taxation should not be corrected in a positive, because according to the Finance Ministry Regulation No. 254 / PMK.03 / 2010 paragraph 1 states that Zakat or compulsory religious donations may be deducted from the gross income. while in the calculation of corporate income tax, the calculation was done by the company is accurate and not experience either error in calculating the number of installments of income tax and income tax payable Article 25Keywords: Fiscal Correction ,Calculation ,Tax Agency